Improving student teaching to better integrate theory and practice - Leroux, Mylène; Andwandter Cuellar, Nathalie; Gélinas-Proulx, Andréanne; Vivegnis, Isabelle (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2023)
This article focuses on the relationship between coursework and field experience, theory and practice. Guided by Korthagen et al.’s (2006) fundamental principles for teacher education, an alternative student teaching structure was tested at the Université du Québec en Outaouais (Canada) in the Fall 2016 term. An online survey was conducted to elicit feedback on how this structure helped enhance the link between theory and practice, according to student teachers, mentor teachers, and teacher educators. Results show the structure offered student teachers the opportunity to reinvest learning in both theory and practice and to discuss the tensions between the two, which represented a significant moment in the program’s development.